3(x-8)+6=27

Simple and best practice solution for 3(x-8)+6=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-8)+6=27 equation:


Simplifying
3(x + -8) + 6 = 27

Reorder the terms:
3(-8 + x) + 6 = 27
(-8 * 3 + x * 3) + 6 = 27
(-24 + 3x) + 6 = 27

Reorder the terms:
-24 + 6 + 3x = 27

Combine like terms: -24 + 6 = -18
-18 + 3x = 27

Solving
-18 + 3x = 27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 3x = 27 + 18

Combine like terms: -18 + 18 = 0
0 + 3x = 27 + 18
3x = 27 + 18

Combine like terms: 27 + 18 = 45
3x = 45

Divide each side by '3'.
x = 15

Simplifying
x = 15

See similar equations:

| 12b-42= | | 2y+6x=26 | | 25x-15=20x-7 | | 50+22/16x=8 | | 2b^2=10b+12 | | 6/7=42/h | | 350-25x=350 | | 2(4-x)-12=36+2x | | 6/2=12/m | | 6k-2=16 | | 5y+4=34 | | 1/8*2= | | x+49=64 | | 2x-3x+4z=8 | | X^7=16384 | | 120-15x=2 | | 18x^3+6x^2-91x-63=0 | | 3x^2+15=315 | | 2(y+4)=3(y-3) | | 0.153x+0.33=0.428-0.846x+0.428 | | 18p=40p-20 | | 150.00x+1000=2200.00 | | 8x+9-7x-5=3x-2x-9 | | 150.00x+1000=30 | | 2(2+2-2)/2*2=0 | | 3+x=24-x | | 6x+4(400-x)=2200 | | p/3+9p | | P/3=112-9P | | -7x^2-7x+4=0 | | 3x+7=2(x+1) | | y=-4/5x+6 |

Equations solver categories